The Inhibition of Plant and Animal Adenosine 3′:5′-Cyclic Monophosphate Phosphodiesterases by a Cell-Division-Promoting Substance from Tissues of Higher Plant Species - Wood, Henry N. (1972)
One member of a new class of cell-division-promoting factors, that has been given the trivial name of cytokinesin I, is a potent inhibitor of adenosine 3′:5′-cyclic monophosphate phosphodiesterases of both plant and animal origin. Since an adenylate cyclase has been demonstrated in this study to be present in plant cells, the results suggest that cytokinesin I may be exerting its biological effects in promoting division in cells of higher plant species as a regulator of adenosine 3′:5′-cyclic monophosphate.